131I-MIBG Therapy in a Metastatic Small Bowel Neuroendocrine Tumor Patient Undergoing Hemodialysis. (May 2017) - Rahimi, Behruz; Makis, William; Riauka, Terence A.; McEwan, Alexander J.B.; Morrish, Don
Abstract : Abstract: Systemic radioisotope therapy with 131 I-metaiodobenzylguanidine ( 131 I-MIBG) is an effective form of targeted therapy for neuroendocrine tumors. One of the absolute contraindications to administering 131 I-MIBG therapy listed in the 2008 European Association of Nuclear Medicine guidelines is renal insufficiency requiring dialysis, although this contraindication is not evidence based. We describe a 68-year-old woman with a metastatic small bowel neuroendocrine tumor who developed renal insufficiency requiring hemodialysis. Imaging and dosimetry with 131 I-MIBG were performed and showed that the radiation doses to the whole body and lungs were within safe limits. She was treated with 1820 MBq of 131 I-MIBG with no short-term adverse reactions.